Modern Trends in Interior Design of Hotel Premises - Nigina Farrukhovna Isroilova; Zafarbek Erkinovich Matniyazov; Yashnar Marufovich Mansurov (Genius Journals, 2022)
The article is devoted to the role of interior design in the activities of hotels, its competitive value. The main trends in hotel design were identified and its impact on consumers of the hotel product was considered. The main directions of introduction of new technologies in the architectural and spatial environment of hotels are noted. The specifics of hotel design development and the principles of combining design ideas with the achievements of information technology are shown. Attention is drawn to the importance of introducing modern technologies for hospitality enterprises
Keywords: Hotel; Comfort; Interior Design; Innovative Technologies